Analysis of the Effect of Discipline Learn and Self-Confidence on Chemistry Learning Achievement - Haryati, Sri; Albeta, Sri Wilda; Sella, Dwi Adheka (International Journal of Scientific Research and Management (IJSRM), 2024)
Research has been conducted with the purpose of identifying the partial and simultaneous influence of discipline learn and self-confidence on student learning achievement in class X chemistry subjects at MA Darul Hikmah Pekanbaru. The kind of research adopted is survey research with quantitative approach. The research was conducted at MA Darul Hikmah Pekanbaru in the even semester of 2023/2034 using random sampling technique using the slovin formula so as to get a research sample of 122 students. Data collection techniques through literature studies and questionnaires. The results showed that discipline learn had a positive and significant reaction on chemistry learning achievement with a contribution of 17.5%, self-confidence had a positive and significant reaction on chemistry learning achievement with a contribution of 14.1%, and discipline learn and self-confidence simultaneously had a positive and significant reaction on chemistry learning achievement with a contribution of 18.2% the remaining part is likely influenced by other aspects not included in this research.